Implementasi Metode Hybrid AHP dan TOPSIS pada Sistem Pendukung Keputusan Pemilihan Lokasi Tempat Pembuangan Sampah Sementara - Bayhaqqi Bayhaqqi; Saiful Bukhori; Gayatri Dwi Santika (INFORMAL: Informatics Journal, 2021)
Temporary Waste Disposal Site (TPSS) is a place to collect waste from various community activities which will later be transported to the final disposal site by garbage trucks. There are many considerations in choosing a TPSS location, so the selection of a TPSS location is very important in supporting the collection of waste that will be transported to final disposal. The Jember Regency Environmental Service is an agency in charge of waste management, including the selection of TPSS locations. Choosing the location of TPSS so far is still manual, where manual selection cannot be separated from human error, so that choosing the location of TPSS is not accurate can cause new problems in the community. In addition, there is no standardized assessment system in the TPSS selection process, so a decision support system is needed that can be used to assist the process of selecting the best TPSS location recommendations. In making this research system, we implemented the hybrid method of AHP and TOPSIS. Where the AHP method is used to determine the weight of the criteria while the TOPSIS method is used for the selection process for TPSS candidates.